IFNγ Enhances CD64-Potentiated Phagocytosis of Treponema pallidum Opsonized with Human Syphilitic Serum by Human Macrophages - Hawley, Kelly L.; Cruz, Adriana R.; Benjamin, Sarah J.; La Vake, Carson J.; Cervantes, Jorge L.; LeDoyt, Morgan; Ramirez, Lady G.; Mandich, Daniza; Fiel-Gan, Mary; Caimano, Melissa J.; Radolf, Justin D.; Salazar, Juan C. (Frontiers in Immunology, 2017)
Syphilis is a multi-stage, sexually transmitted disease caused by the spirochete Treponema pallidum (Tp). Considered broadly, syphilis can be conceptualized as a dualistic process in which spirochete-driven inflammation, the cause of clinical manifestations, co-exists to varying extents with bacterial persistence. Inflammation is elicited in the tissues, along with the persistence of spirochetes to keep driving a robust immune response while evading host defenses; this duality is best exemplified during the florid, disseminated stage called secondary syphilis (SS). SS lesions typically contain copious amounts of spirochetes along with a mixed cellular infiltrate consisting of CD4+ T cells, CD8+ T cells, NK cells, plasma cells and macrophages. In the rabbit model, Tp are cleared by macrophages via antibody (Ab)-mediated opsonophagocytosis. Previously, we demonstrated that human syphilitic serum (HSS) promotes efficient uptake of Tp by human monocytes and that opsonophagocytosis of Tp markedly enhances cytokine production. Herein, we used monocyte-derived macrophages to study Tp-macrophage interactions ex vivo. In the absence of HSS, monocyte-derived macrophages internalized low numbers of Tp and secreted little cytokine (e.g., TNF). By contrast, these same macrophages internalized large numbers of unopsonized Borrelia burgdorferi and secreted robust levels of cytokines. Maturation of macrophages with M-CSF and IFNγ resulted a macrophage phenotype with increased expression of HLA-DR, CD14, iNOS, TLR2, TLR8 and the Fcγ receptors (FcγR) CD64 and CD16, even in the absence of LPS. Importantly, IFNγ-polarized macrophages resulted in a statistically significant increase in opsonophagocytosis of Tp accompanied by enhanced production of cytokines, macrophage activation markers (CD40, CD80), TLRs (TLR2, TLR7, TLR8), chemokines (CCL19, CXCL10, CXCL11) and TH1-promoting cytokines (IL-12, IL-15). Finally, the blockade of FcγRs, primarily CD64, significantly diminished spirochetal uptake and pro-inflammatory cytokine secretion by IFNγ-stimulated macrophages. Our ex vivo studies demonstrate the importance of CD64-potentiated uptake of opsonized Tp and suggest that IFNγ-activated macrophages have an important role in the context of early syphilis. Our study results also provide an ex vivo surrogate system for use in future syphilis vaccine studies.